A Web Searcher Agent Based on Contextual Rules and Collaboration among Agents - Uez, Daniela Maria; Silva, João Luis Tavares da (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2011)
This paper presents a study to develop a Web searcher agent for semantic information retrieval on the Web. This agent uses semantic rules defined by an ontology to filter the search context. For this study a literature search was performed and the agent was developed to test the results. The literature search provides the basis to development of the agent. The agent was developed using the SemantiCore framework and Jena API. The SemantiCore framework was used to develop the agents and its interactions while the Jena API enabled the reading and manipulation of the ontology used for semantic filtering. This study concludes that searching using semantic rules defined by ontologies is a viable alternative to improve web search results.